Using Expressive Writing Tasks in Reducing Students’ Learning Anxieties in an Online Chemistry Class - Angelo Saja; Voltaire M. Mistades (Proceedings Series on Physical & Formal Sciences, 2022)
The abrupt changes in the way how students learn was greatly affected by the covid-19 pandemic. Increasing number of reports on excessive worrying came from students. They had trouble sleeping and expressing their thoughts because of depression, stress, and anxiety. This action research was designed to reduce anxiety of students related to chemistry and taking test in an online learning through expressive writing. A total of twenty-six participants collaborated for a 4-week expressive writing program. Participants baseline measurements of their anxieties were recorded before they undergone a 20-minute writing task every week for the entire duration of the intervention. Data gathered revealed a significant reduction in the anxieties of the participants with medium effect for both chemistry and testing. It has been found out that female participants were significantly more anxious than male for both areas. Interview data revealed that participants’ anxieties were cause by self-doubt and overthinking, experience of failure, lack of prior knowledge and time. However, expressive writing provided sense of achievement, student’s empowerment, opportunity to control emotion, and feeling of relief.